Wildfires mediate carbon transfer from land to lakes across boreal and temperate regions - Mathilde Bélair; Ian M. McCullough; Christopher T. Filstrup; Jennifer A. Brentrup; Jean-François Lapierre (Communications Earth & Environment)
Abstract Wildfires can disrupt carbon transport from land to water, but how lake carbon cycling responds to fires remains unclear. Here, we analyzed the concentration and dominance of the main carbon forms in total carbon pools in 54 lakes (34 burned, 20 control) across 3 regions of Quebec, Canada and Minnesota, USA from recent wildfires ( < 1 – 3 years). Lakes in burned watersheds had up to double the dissolved organic carbon concentrations of control lakes, and the fire effect was most apparent when accounting for climate and landscape drivers (e.g., catchment to lake area ratio) of lake carbon cycling. The greater quantity and dominance of dissolved organic carbon in burned lakes over other carbon forms with different turnover rates and fates suggest a potential fire-mediated carbon export up to several years post fire with a yet undetermined fate in northern forested watersheds and with important implications for regional to global carbon budgets.